(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper discusses the development of models for predicting the thermal conductivity and viscosity of hybrid nanofluids composed of both aluminum oxide (Al2O3) and titanium dioxide (TiO2) nanoparticles. The investigation focuses on how varying the fluid temperature (ranging from 283 K to 298 K) affects the performance of a plate heat exchanger utilizing Al2O3-TiO2 hybrid nanofluids with different particle volume ratios (0:5, 1:4, 2:3, 3:2, 4:1, and 5:0). These nanofluids are prepared with a 0.1% concentration in deionized water. Experimental assessments are conducted to evaluate several key parameters, including heat transfer rate, Nusselt number, heat transfer coefficient, Prandtl number, pressure drop, and performance index. The study findings reveal noteworthy trends. As the TiO2 ratio increases, there is a decrease in the heat transfer coefficient, Nusselt number, and heat transfer rate. This decline can be attributed to the lower thermal conductivity of TiO2 in comparison to Al2O3. Conversely, an increase in the inlet temperature leads to a decrease in pressure drop and the performance index. Remarkably, the Al2O3 (5:0) nanofluid demonstrates the most significant enhancement, with improvements of approximately 16.9% in the heat transfer coefficient, Nusselt number, heat transfer rate, and performance index. On the other hand, the TiO2 (0:5) hybrid nanofluid exhibits modest enhancements of 0.61% and 2.3% for pressure drop and Prandtl number, respectively.